Neurosteroid-based intervention using Ganaxolone and Emapunil for improving stress-induced myelination deficits and neurobehavioural disorders. (November 2021) - Crombie, Gabrielle K.; Palliser, Hannah K.; Shaw, Julia C.; Hodgson, Deborah M.; Walker, David W.; Hirst, Jonathan J.
Abstract: Background: Prenatal stress is associated with long-term disturbances in white matter development and behaviour in children, such as attention deficit hyperactivity disorder (ADHD) and anxiety. Oligodendrocyte maturation and myelin formation is a tightly orchestrated process beginning during gestation, and therefore is very vulnerable to the effects of maternal prenatal stresses in mid-late pregnancy. The current study aimed to examine the effects of prenatal stress on components of the oligodendrocyte lineage to identify the key processes that are disrupted and to determine if postnatal therapies directed at ameliorating white matter deficits also improve behavioural outcomes. Methods: Pregnant guinea pig dams were exposed to control-handling or prenatal stress with strobe light exposure for 2hrs/day on gestational age (GA) 50, 55, 60 and 65, and allowed to spontaneously deliver ~GA70. Pups were administered oral ganaxolone (5 mg/kg/day in 45% cyclodextrin) or the TSPO agonist, emapunil (XBD173; 0.3 mg/kg/day in 1% tragacanth gum) or vehicle, on postnatal days (PND) 1–7. Behavioural outcomes were assessed using open field and elevated plus maze testing on PND7 and PND27. Hippocampal samples were collected at PND30 to assess markers of oligodendrocyte development through assessment of total oligodendrocytes (OLIG2) and mature cells (myelin basic protein; MBP), and total neurons (NeuN) by immunostaining. Real-time PCR was conducted on hippocampal regions to assess markers of the oligodendrocyte lineage, markers of neurogenesis and components of the neurosteroidogenesis pathway. Plasma samples were collected for steroid quantification of cortisol, allopregnanolone, progesterone and testosterone by ELISA. Results: Prenatal stress resulted in hyperactivity in male offspring, and anxiety-like behaviour in female offspring in the guinea pig at an age equivalent to late childhood. Postnatal ganaxolone and emapunil treatment after prenatal stress restored the behavioural phenotype to that of control in females only. The oligodendrocyte maturation lineage, translation of MBP mRNA-to-protein, and neurogenesis were disrupted in prenatally-stressed offspring, resulting in a decreased amount of mature myelin. Emapunil treatment restored mature myelin levels in both sexes, and reversed disruptions to the oligodendrocyte lineage in female offspring, an effect not seen with ganaxolone treatment. Conclusion: The marked and persisting behavioural and white matter perturbations observed in a clinically relevant guinea pig model of prenatal stress highlights the need for postnatal interventions that increase myelin repair and improve long-term outcomes. The effectiveness of emapunil treatment in restoring female offspring behaviour, and promoting maturation of myelin indicates that early therapeutic interventions can reverse the damaging effects of major stressful events in pregnancy. Further studies optimising target mechanisms and dosing are warranted. Highlights: Stress during pregnancy disrupts behaviour in guinea pig offspring at an age equivalent to childhood. Stress-induced behavioural alterations involve alterations to the oligodendrocyte lineage pathway and myelin. Therapeutics that target the neurosteroid pathway are able to restore female offspring behaviour to control levels. Improvements in mature myelin coverage with neurosteroid treatments are likely linked to improvements in behaviour.